IoT-Based Seismic Sensor Network Design for Early Warning System in Kalimantan : Literature Review - Ilham Muthahhari; Muhammad Dzakwan Firdaus (Yayasan Kita Menulis - JoCPES, 2024)
Kalimantan is not commonly associated with significant seismic activity due to its relative distance from major tectonic plate boundaries; however, it remains vulnerable to earthquakes that pose risks to human safety and the integrity of infrastructure. A recent seismic incident in the region has raised alarms about the adequacy of current preparedness and mitigation measures. This review seeks to establish a robust early warning system (EWS) for earthquakes by incorporating seismograph technology and IoT-based sensor networks tailored for Kalimantan. Despite its traditional classification as a low-seismic area, the region is susceptible to risks stemming from nearby active faults and tectonic dynamics. By analyzing recent research, this paper highlights the distinct geographical and environmental factors that must be considered when implementing a seismic sensor network in Kalimantan. It also examines the critical elements of seismographic devices for earthquake detection and discusses the role of IoT in enhancing real-time monitoring and early warning capabilities. The proposed IoT-based EWS utilizes affordable, distributed sensors to improve response times and detection precision, thereby providing timely notifications to vulnerable areas. This strategy presents a scalable and economically viable model for regions at risk of earthquakes, emphasizing the significance of both sophisticated instrumentation and accessible IoT technology for communities.